أثر التنويع الإقتصادي على النمو الإقتصادي خارج قطاع المحروقات في الجزائر - يونسي, فاطمة (My University, 2019)
This study aims to measure the impact of the economic diversification on the economic growth in algeria during the years 1990 – 2016 in order to highlight the importance of diversification to achieve high levels in the economic growth . Algeria as a country that depends totally on the revenues of oil in its oil industries is facing the risk of instability considering the decrease in oil prices which the international markets currently suffer from. This shows the need of the Algerian econmy to adapt diversification in its sources of incomes, and to build a stable economy that relies on a diversified base of strong economic resoirces. As, different sectors must be activated and increase thier contribution to the Gross domestic product (GDP).
دراسة قياسية 1990-2016
Keywords: التنوع الإقتصادي ، النمو الإقتصادي ، الناتج المحلي الإجمالي ، دراسة قياسية 1990-2016